판타지 드라마 주인공의 초현실적 능력과 몰입: 의사사회적 상호작용과 판타지 충족감의 매개 역할 - 임인재; 김승현; 나은영 (Journal of Communication Research, 2019)
본 연구는 판타지 드라마 주인공의 초현실적 능력이 드라마 몰입에 어떤 영향을 미치는지 살펴보고, 그 과정에서 의사사회적 상호작용과 판타지 충족감이 매개효과를 보이는지 분석하였다. 실험 1에서는 드라마 ‘도깨비’에서 주인공의 초현실적 능력이 높은 장면과 낮은 장면을 추출한 뒤 330명을 대상으로 유사 실험 연구를 진행했다. 그 결과, 주인공의 초현실적 능력은 드라마 몰입도에 정적인 영향을 미쳤으며, 그 과정에서 의사사회적 상호작용은 매개효과를 보이지 않았지만 판타지 충족감은 부분적인 매개효과를 보였다. 실험 1의 단점을 보완하고 결론의 일반화 가능성을 높이기 위해 실험 2에서는 ‘도깨비’보다 상대적으로 시청률과 인지도가 낮은 판타지 드라마 ‘별에서 온 그대’, ‘W(더블유)’를 선정해 유사 실험 연구를 진행했다. 각 드라마에서 주인공의 초현실적 능력이 높은 장면과 낮은 장면을 추출해 설문을 실시한 결과(N=320), 집단(고초능력 집단 vs 저초능력 집단) 에 따라 드라마 몰입도 차이가 유의미하여, 등장인물의 초현실적 능력이 높을수록 드라마 몰입도가 높아졌다. 의사사회적 상호작용과 판타지 충족감은 각각 부분 매개 효과를 보였다. 초현실적 능력을 보이는 등장인물은 의사사회적 상호작용을 매개로 몰입도에 부정적인 영향을, 판타지 충족감을 매개로 몰입도에 긍정적인 영향을 미쳤다. This study explored the effect of protagonists’ surrealistic power for the immersion in fantasy drama and analyzed the mediation effect of parasocial interaction and fantasy fulfillment. Through the study 1, we extracted several scenes which shows protagonists’ high and low surrealistic power from the soap opera ‘Goblin’ and searched the quasi-experiment study for 330 subjects. It came down to the following conclusions. First, it has shown that protagonists’ surrealistic power effects on the immersion positively and fantasy fulfillment has the mediation effect partially even though parasocial is not related to the mediation effect. In Study 1, considering the fact that there was no difference among the groups(high surrealistic power vs low surrealistic power) due to the high awareness of the participants, in Study 2, we conducted a quasi- experiment study by selecting the fantasy drama ‘My Love from the Star’ and ‘W(W)’, which have a relatively lower viewer ratings than ‘Goblin’. As a result of the surveys (N= 320), we found that the drama immersion difference was significant according to the group(high surrealistic power vs low surrealistic power). The higher the surrealistic power of the drama, the higher the drama immersion. Parasocial interaction and fantasy fulfillment were partially mediated. The characters with surrealistic ability had a negative influence on immersion through mediation of parasocial interaction, and positive influence on immersion through mediation of fantasy fulfillment. KCI Citation Count: 0